Development of Centrifugal Disc Spreader on Tracked Combine Harvester for Rape Undersowing Rice Based on DEM - Zhuohuai Guan; Senlin Mu; Tao Jiang; Haitong Li; Min Zhang; Chongyou Wu; Mei Jin (Agriculture, 2022)
Rape undersowing rice is an effective method to solve the problem of short crop rotation in rice-rape rotation. Applying of ground fertilizer to rape is one of the most critical aspects in this planting pattern. However, a special fertilizer spreading is required after the rice is harvested, which increases the labor intensity and the compaction of rape and soil and is also hindered by a lack of equipment to complete the harvesting and fertilizer spreading simultaneously. In response to the above issues, a centrifugal disc spreader on a tracked combine harvester for rape undersowing rice was developed. The basic parameters of the spreader were designed based on the agronomic requirements for fertilization and tracked combine harvester. Kinematic and kinetic models of fertilizer particles were developed to determine the key parameters that affect fertilizer spreading. Based on discrete element simulations, the effects of single structure and interaction of centrifugal disc spreader on fertilizer distribution pattern were investigated. The spreading range and coefficient of variation of fertilizer lateral distribution regression models were constructed, and the spreader parameters were optimized based on the regression models. The simulation results and fertilizer spreading performance were verified by bench tests. The results show that the distribution of fertilizer from simulation tests and bench tests was consistent. The coefficient of variation of fertilizer lateral distribution was 13.1% for the simulation test and 14.6% for the bench test. The error of simulation test was 10.3%, which indicates that the simulation result was reliable. The developed centrifugal disc spreader can meet the needs of fertilizer spreading for rape undersowing rice. The results serve as a theoretical basis for the design of a fertilizer spreader and provide new ways to promote accurate and efficient spreading of fertilizer.